2019
DOI: 10.1021/acs.iecr.9b05779
|View full text |Cite
|
Sign up to set email alerts
|

Strong Influence of Amine Grafting on MIL-101 (Cr) Metal–Organic Framework with Exceptional CO2/N2 Selectivity

Abstract: Matérial Institut Lavoisier (MIL)-101, one of the metal–organic frameworks containing numerous coordinatively unsaturated sites, as well as high specific surface area, was synthetized under different protocols for CO2 adsorption and separation from N2. To improve its CO2 adsorption capacity, different amounts [10, 25, and 40 wt % of tetraethylenepentamine (TEPA)] were grafted to the parental MIL-101. Results revealed that TEPA-MIL-101 (40 wt %) showed one of the highest CO2 adsorption capacities (i.e., 3.76 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…Though the sorption capacity is somewhat small, it is worth to note that the remarkable selectivity of CO 2 /N 2 far exceeds those of many reported MOFs, such as ZnF(daTZ) (120), [26] UTSA-85a (62.5), [27] and TEPA-MIL-101 (40 wt %) (220). [28] Overall, the impressive adsorption selectivity indicates that the framework of UPC-601 can form stronger interactions with CO 2 and C 2 H 2 than CH 4 or N 2 , making it potential candidate for CO 2 capture from flue gas and natural gas purification.…”
Section: Angewandte Chemiementioning
confidence: 98%
“…Though the sorption capacity is somewhat small, it is worth to note that the remarkable selectivity of CO 2 /N 2 far exceeds those of many reported MOFs, such as ZnF(daTZ) (120), [26] UTSA-85a (62.5), [27] and TEPA-MIL-101 (40 wt %) (220). [28] Overall, the impressive adsorption selectivity indicates that the framework of UPC-601 can form stronger interactions with CO 2 and C 2 H 2 than CH 4 or N 2 , making it potential candidate for CO 2 capture from flue gas and natural gas purification.…”
Section: Angewandte Chemiementioning
confidence: 98%
“…VOCs, including aromatics, alkanes, amines, and oxygenated or halogenated hydrocarbons [ 4 , 5 , 6 ], are often produced by chemical and pharmaceutical industries [ 7 , 8 , 9 ]. Porous materials currently used for adsorbing VOCs are zeolites (Zs) [ 10 , 11 , 12 ], activated carbons (ACs) [ 13 , 14 , 15 , 16 ], polymeric resins (PRs) [ 17 , 18 , 19 , 20 ], and metal-organic frameworks (MOFs) [ 21 , 22 , 23 , 24 ]. In these systems, a pre-drying column to remove the moisture of absorbed chemicals is generally required to maintain the adsorbing efficiency [ 24 ], which is an additional cost for VOC adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…The regeneration energy was also low due to its low heat capacity, which was better than amine grafted silica and amine aqueous solution. Pirzadeh et al 98 grafted different amounts of tetraethylenepentamine (TEPA) to the parental MIL-101. The results showed that TEPA-MIL-101 (40 wt%) had one of the largest CO 2 adsorption capacity (3.76 mmol g −1 at 298 K, 1 bar) with 1.56 times higher than that of MIL-101 among the existing MIL-101 and its modified components, as well as the good CO 2 cyclic adsorption stability, as shown in Fig.…”
Section: Modification Methods Of Mofs For Co2 Capturementioning
confidence: 99%